KORELASI JUMLAH PASIEN RAWAT INAP DENGAN KONSUMSI OKSIGEN CAIR DI RSUP DR.M.DJAMIL PADANG - Catur Suharinto; Viola Shinta Dewi; Zarni Zamzahar; Chindy Violeta S (LLDIKTI Wilayah X, 2023)
In the last two years, the world has been preoccupied with the outbreak of the Coronavirus Disease 2019 (COVID 19) infection, which is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). During the COVID-19 pandemic, the increasing use of oxygen caused a new problem, namely oxygen supply. The large number of patients who need a ventilator at the same time can endanger the oxygen supply.This research is a quantitative study. The sample in this study was taken as a total population, namely the number of inpatients per day at RSUP Dr. M. Djamil in 2021. The research was conducted from July to December 2022. Data analysis used SPSS by looking at bivariate correlation analysis. The results of the univariate analysis found that oxygen use during 2021 at RSUP Dr.M.Djamil Hospital Padang was 1351.5m3. The number of inpatients during 2021 at RSUP Dr.M.Djamil Padang was 164,207 patients, inpatients with covid (14.86%) and non-covid (85.14%). Based on the statistical test results, it is known that there is a correlation between the variable number of inpatients (covid, intensive covid, non-incentive covid, non-covid, non-intensive covid, non-intensive covid (0.001).There is a correlation between the number of hospitalized patients and liquid oxygen consumption. It is hoped that the hospital can improve services in dealing with Covid-19 at RSUP Dr. M. Djamil Padang especially in making policies related to the management of oxygen availability. The public is expected to comply with health protocols so that the handling of Covid-19 cases does not occur out of control. Keywords : COVID-19;Oxygen;Inpatient;Correlation